DAMPAK KRISIS MONETER DAN KEBIJAKSANAAN PEMERINTAH TERHADAP DAYA SAING AGRIBISNIS AYAM RAS PEDAGING DI JAWA BARAT - -, SAPTANA; RUSASTRA, I WAYAN (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Monetary and economic crisis started on the mid of 1997 has negative impact on the performance and sustainability of poultry industry in this country. The main problem faced by broiler industry, namely: (1) Most of feed stuff are highly dependent on import; (2) The structure of input and output market are olygopolistic in nature; (3) Cooperative farming is not consistently implemented; and (4) The price of input factor increased threefold due to monetary and economic crisis. Based on those backgrounds, the objective of this study is to analysis the impact of government policy on financial and economic feasibilities of broiler agribusiness. The finding of the respective study conducted in two district (Bogor and Tasikmalaya) indicated that: (1) Because of economic crisis, financial and economic profitability of broiler industry decreases; (2) Private Cost Ratio (PCR) increased from 0,753 – 0,873 to 0,851 – 0,989 due to crisis, indicating lower financial competitiveness; (3) The value of DRCR before and after crisis are 0,727 – 0,976 vs. 0,790 vs. 0,917 which reveal lower economic competitiveness; and (4) The value of Nominal Protection Coefficient (NPC) during the economic crisis showed that broiler industry experiencing disincentive for both input and output market. The implication of this study in relation with the development of broiler industry facing the economic globalization are as follows: (1) The vertical integration and cooperation between smallholder broiler farming and input/output industry should be strengthening in synergistic manner; (2) In order to generate foreign exchange and higher value added through export and product development as well as product differentiation, vertical integration for all agribusiness subsystem in broiler industry should be implemented; and (3) The establishment of cooperative broiler farming system should be conducted in the regional news of potential market and feed stuff producing regions.
Keywords: Monetary Crisis, Competitiveness, Government Policy, and Broiler Agribusiness